2008
DOI: 10.1111/j.1460-9568.2008.06256.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation reduces mechanical thresholds in a population of transient receptor potential channel A1‐expressing nociceptors in the rat

Abstract: Inflammatory hypersensitivity is characterized by behavioural reductions in withdrawal thresholds to noxious stimuli. Although cutaneous primary afferent neurones are known to have lowered thermal thresholds in inflammation, whether their mechanical thresholds are altered remains controversial. The transient receptor potential channel A1 (TRPA1) is a receptor localized to putative nociceptive neurones and is implicated in mechanical and thermal nociception. Herein, we examined changes in the properties of sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
73
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 74 publications
5
73
0
Order By: Relevance
“…Similar to the cinnamaldehyde effect, Inoue et al (1997) reported that the plasma extravasation evoked after reapplication of the TRPA1 receptor agonist, allyl isothiocyanate, on days 1, 3 and 7 was not different from that induced after its initial application. Moreover, Dunham et al (2008) also failed to detect sensitization or desensitization to cinnamaldehyde-induced activation of primary afferent fibers in rats when the stimulus was injected each 5 min. On the other hand, other studies were capable of detecting desensitization to allyl isothiocyanate-induced currents in sensory neurons, neuropeptide release in skin or nociception in rats when the interstimuli interval was from 3 to 20 min (Akopian et al, 2007;Ruparel et al, 2008).…”
Section: Discussionmentioning
confidence: 79%
“…Similar to the cinnamaldehyde effect, Inoue et al (1997) reported that the plasma extravasation evoked after reapplication of the TRPA1 receptor agonist, allyl isothiocyanate, on days 1, 3 and 7 was not different from that induced after its initial application. Moreover, Dunham et al (2008) also failed to detect sensitization or desensitization to cinnamaldehyde-induced activation of primary afferent fibers in rats when the stimulus was injected each 5 min. On the other hand, other studies were capable of detecting desensitization to allyl isothiocyanate-induced currents in sensory neurons, neuropeptide release in skin or nociception in rats when the interstimuli interval was from 3 to 20 min (Akopian et al, 2007;Ruparel et al, 2008).…”
Section: Discussionmentioning
confidence: 79%
“…The symbols "þ" indicate a response significantly greater than that induced by 0.9% NaCl (t test, p < 0.05). Dunham et al, 2008;Eid et al, 2008;Obata et al, 2005;Petrus et al, 2007) and by in vitro studies showing sustained TRPA1 activation using the perforated patch clamp technique (Koivisto et al, 2012) and intracellular calcium images (Koivisto et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…In vitro studies demonstrate that TRPA1 plays as a mechanosensor in DRG and the mechanical thresholds of the TRPA1-positive neurons are lowered with somatic inflammation [20]. Either genetically knocking down TRPA1 or the administration of specific antagonists for TRPA1 could attenuate such mechanical hyperalgesia in certain inflammatory and nerve injury models [16,30,36].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the role of TRPA1 in the field of gut sensation arouses recent interest of researchers. It is reported that TRPA1 plays as a mechanosensor [20] and TRPA1 deletion markedly reduced colitis-induced mechanical hyperalgesia in the mice [21]. However, whether TRPV1 and TRPA1 channels are involved in the altered visceral sensation in the chronic psychological stress is not yet evident.…”
Section: Introductionmentioning
confidence: 95%